Environmental and cost life-cycle approach to support selection of windows in early stages of building design. (20th August 2022) - Saadatian, Shiva; Rodrigues, Carla; Freire, Fausto; Simões, Nuno
Abstract: The selection of windows with the lowest life-cycle environmental impacts in an early-design stage is important to minimize impacts of buildings. Hence, an environmental and cost streamlined life-cycle assessment (LCA) approach, incorporating probabilistic triage, has been developed to support early-decision making for selection of window materials and components. This approach permits also to reduce the uncertainty in the estimated results by means of sequentially specifying attributes based on the attribute ranking. For demonstration purposes, a large number of window alternatives has been assessed for a reference office room. This approach proved to be effective in providing robust results to support the selection of windows by specifying very few window-related attributes (less than 8). The attribute ranking results show that the most influential attributes in terms of cost and environmental LCA are window-to-wall ratio and orientation, respectively. Future market window solutions with a wide range of alternative materials and components, impacting thermal transmittance and solar factor values, can be assessed using this approach to find optimal cost and environmental performance of buildings. Highlights: A large number of window alternatives assessed by a streamlined LCA approach. Sequentially specified attributes analysis based on attribute ranking. Robust early-stage decisions based on few specified attributes. The most influential attributes are window-to-wall ratio and orientation. Streamlined LCA approach to select future windows for a wide range of parameters.